Genetic Correlations and Path Analysis in Butternut Squash Cucurbita moschata Duch (2015)
Abstract. A genetic correlation and path analysis was carried out for yield and fruit quality components of diallel crosses of butternut squash Cucurbita moschata Duch, using openpollinated introductions, S0 and inbred lines S1 and S2 at two sites: Candelaria and Buga, located in the Department of Valle del Cauca, Colombia. A split-plot experimental design with arranged, random blocks and four replicates was used. The average fruit weight presented positive genetic correlations with the total production per plant in all three generations and at both test sites. The total plant dry matter and total production per plant presented a high genetic correlation, and the fruit dry matter was inversely correlated with the total carotene. The total carotene and fruit color were independent. The path analysis confirmed high genetic correlations between the number of fruits per plant, average fruit weight, and total plant dry matter, with direct, positive effects, that were significantly greater than zero for the variables of number of fruits per plant and average fruit weight in regards to the total plant dry matter. The total production per plant expressed a direct, negative effect on the total plant dry matter. The fruit dry matter presented an indirect, negative effect on the total plant dry matter through the average fruit weight and an indirect, positive effect through the total production per plant. / Resumen. Se estudiaron las correlaciones genéticas y el análisis de sendero para los componentes del rendimiento y calidad del fruto de zapallo Cucurbita moschata Duch, en cruzamientos dialélicos entre introducciones de libre polinización S0 y sus líneas S1 y S2 en dos localidades, Candelaria y Buga, ubicadas en el Departamento del Valle del Cauca, Colombia. Se usó un diseño experimental en parcelas divididas, arregladas en bloques al azar con cuatro repeticiones. El peso promedio del fruto presentó correlación genética positiva con producción por planta en las tres generaciones y las dos localidades consideradas. La materia seca por planta y producción por planta presentaron correlación genética alta, la materia seca del fruto estuvo inversamente asociado con caroteno total. El caroteno total y color de fruto manifestaron independencia. El análisis de sendero confirmo correlaciones genéticas altas entre número de frutos por planta, peso promedio del fruto y materia seca por planta con efectos directos positivos y significativamente mayores que cero para las variables número de frutos por planta y peso promedio del fruto sobre la materia seca por planta. La producción por planta expresó efecto directo negativo sobre materia seca por planta. La materia seca del fruto presentó un efecto indirecto negativo sobre materia seca por planta vía peso promedio del fruto y un efecto indirecto positivo a través de producción por planta.